"Ilustrowany Kurier Polski” - dziennik Stronnictwa Demokratycznego (1950-1990) (Kronika Bydgoska, 2010)
Published in Bydgoszcz starting from October 1945, the daily paper “Ilustrowany Kurier Polski” - originally the press organ of the Labour Party (SP) - due to ownership transformations, it belonged to the Democratic Party (SD) from July 12, 1950. It was one of the most popular daily newspapers in the city, and its daily circulation was over 100,000 copies (in the 1970’s). It was the paper of SD until November 29, 1991. In the years 1991-2002, it belonged to private publishers. Systematically loosing readers, the last number was published on December 9, 2002.